A multistep Steffensen‐type method for solving nonlinear systems of equations. (29th April 2019) - Amat, Sergio; Argyros, Ioannis K.; Busquier, Sonia; Hernández‐Verón, Miguel A.; Magreñán, Á. Alberto; Martínez, Eulalia
Abstract : This paper is devoted to the semilocal analysis of a high‐order Steffensen‐type method with frozen divided differences. The methods are free of bilinear operators and derivatives, which constitutes the main limitation of the classical high‐order iterative schemes. Although the methods are more demanding, a semilocal convergence analysis is presented using weaker conditions than the classical Steffensen method.